2011
DOI: 10.1007/s00134-011-2418-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with peripherally inserted central venous catheter-related large vein thrombosis in neurological intensive care patients

Abstract: Alterations in blood flow and consistency, but not vessel injury, appear associated with symptomatic thrombosis following placement of PICCs in neurological intensive care patients. Mannitol use and placement in a paretic arm are potentially modifiable risk factors. Given the high incidence rate of symptomatic thrombosis, future studies should focus on comparing cumulative complications of centrally inserted venous catheters and PICCs in intensive care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 23 publications
2
57
1
Order By: Relevance
“…For example, as has been previously reported, we found that patients with a history of VTE and those undergoing surgery with a PICC in place are more likely to develop thrombosis [7,15,21]. However, we add to this literature by reporting that both short and longer-duration surgical interventions appear to increase this risk, a finding previously not recognized in the literature.…”
Section: Discussionsupporting
confidence: 55%
“…For example, as has been previously reported, we found that patients with a history of VTE and those undergoing surgery with a PICC in place are more likely to develop thrombosis [7,15,21]. However, we add to this literature by reporting that both short and longer-duration surgical interventions appear to increase this risk, a finding previously not recognized in the literature.…”
Section: Discussionsupporting
confidence: 55%
“…Symptomatic venous thrombosis occurs in fewer than 10% of patients with PICC lines 5-7 , but the overall rate of thrombosis, including both symptomatic and asymptomatic, reaches an astounding 38% 8 . The risk of venous thrombosis associated with PICC lines is two-fold higher in patients with chronic kidney disease (CKD) as compared to those with normal kidney function 9 .…”
mentioning
confidence: 99%
“…Lobo et al, 5 in a retrospective study of 777 patients, reported an incidence rate of 4.89%, while Evans et al 6 and King et al 7 reported incidence rates of 3% and 2%, respectively. Wilson et al, 8 in a retrospective study of 431 PICC placements, found the incidence rate of symptomatic thrombosis to be 8.4%. In a retrospective review of 2063 patients with PICC insertions, Chemaly et al 9 reported 52 PICC-associated VTEs, resulting in an incidence rate of 2.47%.…”
Section: Review Of the Literaturementioning
confidence: 98%